Exploring the Landscape of marketing performance of MSMEs in the era of digital transformation: A Bibliometric Analysis - Pradianto, Mi’raj Akbar; Sugiarto, Catur; Amperawati, Endang Dwi; Sabila, Isnayni; Rahmawati, Rahmawati (Indonesian Journal of Sustainability Accounting and Management, 2025)
This study explores the marketing performance of MSMEs in the digital transformation era through bibliometric and cartographic analysis. It is guided by four main research questions: (1) What trends have been observed in publications related to digital entrepreneurship for people with disabilities over the years? (2) Which authors and countries have made the most significant contributions to the literature on digital entrepreneurship for people with disabilities? (3) Which journals have published the most articles on this topic? and (4) What are the most common keywords in the literature on digital entrepreneurship for people with disabilities? The study uncovers trends, key contributors, leading journals, and common themes in the marketing performance of MSMEs in the digital transformation era. Additionally, through cartographic analysis using VOSviewer, it visualizes the relationships and collaboration networks among authors, countries, and keywords, providing a comprehensive view of the global research landscape in this important field. By highlighting existing research and its dynamics, the study enhances the understanding of digital entrepreneurship in the disability context and guides future research and policy efforts to improve the marketing performance of MSMEs in the digital transformation era.